(untitled) (REMUNOM, 2024)
Abstract Periodontitis, a chronic inflammatory oral disease, has been shown to be associated with the development of cardiovascular diseases, such as atherosclerosis, myocardial infarction, and stroke. Multiple theories have been proposed to explain this association, including the direct action of periodontal microorganisms, immunological phenomena, and shared genetic mechanisms. Inflammation plays a significant role in both conditions, contributing to the progression of atherosclerosis and the instability of atherosclerotic plaques. Although treatment of periodontal disease may help prevent cardiovascular diseases, further studies are needed to fully understand this complex relationship and to guide effective prevention and treatment strategies. Interdisciplinary collaboration between oral health professionals and cardiologists is essential to address these comorbid conditions and reduce their impact on public health. Keywords: Periodontitis, Cardiovascular Diseases, Inflammation; Oral Health.